Two new species of the genus Chibiraga Matsumura, 1931 (Lepidoptera: Limacodidae) from China - Ji, Shuqin; Huang, Siyao; Ma, Lijun; Wang, Min (Zootaxa, 2018)
Two new species in the genus Chibiraga, C. houshuaii sp. nov. and C. yukei sp. nov., are described based on specimens collected in Yunnan Province and Sichuan Province, respectively. Illustrations depicting male adults and male genitalia are provided, along with venation patterns and a distribution map of the genus Chibiraga. COI DNA fragments of C. yukei sp. nov. and both sexes of C. banghaasi (Hering & Hopp, 1927) are also depicted.